Fear, justice & modern true crime - Cecil, Dawn K. (Lynne Rienner Publishers, 2020)
True crime obsession -- The serial effect -- Modern true crime -- Serial killers and notorious murderers -- Missing persons and unsolved murders -- Wrongful conviction narratives -- Fear, justice, and the experience of modern true crime.